0491 Prevalence and Predictors of Obesity Hypoventilation Syndrome in the Bariatric Surgery Population. (12th April 2019) - Tran, Katie; Wang, Lu; Gharaibeh, Sae'da; Kempke, Nancy; Aboussouan, Loutfi; Mehra, Reena
Abstract: Introduction: Although obesity hypoventilation syndrome (OHS) is associated with increased morbidity and mortality post-bariatric surgery, there is limited characterization of OHS predictors in this population. We hypothesize that patients referred for bariatric surgery with OHS are more likely to have a greater severity of obstructive sleep apnea (OSA) and metabolic derangements compared to their eucapnic counterparts. Methods: 1114 patients undergoing polysomnography (PSG) with end-tidal CO2 monitoring prior to bariatric surgery at Cleveland Clinic from September 2011 to September 2018 were included. OHS was defined by body mass index (BMI)≥ 30kg/m 2 and either PSG-based end-tidal CO2 (EtCO2)≥ 45mmHg or serum bicarbonate levels≥ 27mEq/L. Univariable and multivariable logistic regression models (OR[95%CI]) were used to examine OHS predictors consisting of factors in domains of patient characteristics, polysomnography (cardiorespiratory and sleep architecture), laboratory and metabolic parameters. Results: The analytic sample was comprised of 1114 patients: age 43.9±12.1 years, 11.6% male, BMI=47.8±8.6kg/m 2, and 62.7% Caucasian. OHS prevalence was 65.6%. Univariable logistic regression analyses revealed odds of OHS increased by 7% (1.07: 1.02, 1.13) per 5-year increase in age; increased by 2% (1.02: 1.00, 1.03) per 5-unit increase in stage shift; increased by 7% (1.07: 1.01, 1.13) per 5% increase in sleep time SaO2<90%; decreased by 2% (0.98: 0.97, 0.99) per unit increase in maximum heart rate during sleep; and increased by 17% (1.17: 1.04, 1.31) per unit increase in hemoglobin A1c; the latter which persisted despite adjustment for age, sex, race, and BMI (1.13: 1.00, 1.27). A 5% increase in odds of OHS per 10% increase in AHI decile was observed: (1.05: 1.00, 1.09). Conclusion: In this well-phenotyped clinic-based cohort, two-thirds of patients referred for bariatric surgery had OHS. Impaired long-term glucose control (even after adjustment for factors including obesity) was one of the strongest OHS predictors, as were alterations in sleep-related cardiopulmonary physiology and increasing age. These important findings can inform risk stratification for OHS in those undergoing bariatric surgery and set the stage for experimental studies to examine sleep-related respiratory and metabolic hypoventilation contributions. Support (If Any): Cleveland Clinic Neurological Institute Transformative Neuroscience Development Award